Prophylactic and Therapeutic Roles of Oleanolic Acid and Its Derivatives in Several Diseases - Sen, Alaattin (Baishideng Publishing Group inc, 2020)
Oleanolic acid (OA) and its derivatives are widely found in diverse plants and are naturally effective pentacyclic triterpenoid compounds with broad prophylactic and therapeutic roles in various diseases such as ulcerative colitis, multiple sclerosis, metabolic disorders, diabetes, hepatitis and different cancers. This review assembles and presents the latestin vivoreports on the impacts of OA and OA derivatives from various plant sources and the biological mechanisms of OA activities. Thus, this review presents sufficient data proposing that OA and its derivatives are potential alternative and complementary therapies for the treatment and management of several diseases.
Sen, Alaattin/0000-0002-8444-376X;
Keywords: Oleanolic Acid; Prophylactic; Anti-Inflammatory; Anti-Diabetics; Neuroprotective; Hepatoprotective